(untitled) (Журналистика сериясы, 2016)
В статье рассматриваются проблемы книжного дела и книгораспространения в Казахстане. Приведены процентные показатели НДС зарубежных и отечественных книг. Автор обрашает внимание на отсутствие нормативно-правовой базы отрасли и логистики в казахстанском книгоиздательском деле. Анализируются законодательные аспекты и мировой опыт государственной поддержки издательского дела и книгораспространения. In the article the problems of book business and knigorasprostraneniya are examined in Kazakhstan. The percent indexes of VATof foreign and domestic books are resulted. Author obrashaet attention on absence of normative-legal base of industry and logistic on Kazakhstan publishing business. Legislative aspects and world experience of state support of publishing business and knigorasprostraneniya are analysed.